(E)-4-Hydroxy-N′-(2-methoxybenzylidene)benzohydrazide - Rassem, Hesham Hussein (International Union of Crystallography, 2012)
In the title compound, C(15)H(14)N(2)O(3), the dihedral angle between the benzene rings is 66.56 (5)°. In the crystal, N—H⋯O, O—H⋯O and C—H⋯O interactions link the molecules into a three-dimensional network. A π–π interaction, with a centroid–centroid distance of 3.628 (6) Å, helps to establish the packing.